Herpetological results of Francisco Newton’s Zoological Expedition to Angola (1903–1906): a taxonomic revision and new records of a forgotten collection - Santos, Bruna S.; Marques, Mariana P.; Bauer, Aaron M.; Ceríaco, Luis M. P. (Zootaxa, 2021)
Francisco Newton’s zoological expedition to Angola undertaken between 1903 and 1906 is one of the least studied of the naturalist’s life. Only three major papers regarding the herpetofauna collected in this expedition have been published, and a significant part of the specimens remains unstudied since the 1900’s. Here we review the extant herpetological specimens of this expedition, present an updated taxonomic revision, and provide new insights on their taxonomic status. The extant collection is constituted by 329 specimens (155 amphibians and 174 reptiles), corresponding to 73 species, 39 genera and 22 families, and it is presently housed in the Museu de História Natural e da Ciência da Universidade do Porto (MHNC-UP).